Nobiletin Ameliorates the Deficits in Hippocampal BDNF, TrkB, and Synapsin I Induced by Chronic Unpredictable Mild Stress - Li, Jing (Hindawi Publishing Corporation, 2013)
Background. Our previous study has demonstrated that nobiletin could reverse the behavioral alterations in stressed mice. However, the relation of its antidepressant-like action with neurotrophic molecular expression remains unknown. This study aimed to explore the antidepressant-like mechanism of nobiletin related to the neurotrophic system in rats exposed to chronic unpredictable mild stress (CUMS). Methods. Depressive-like anhedonia (assessed by sucrose preference) and serum corticosterone secretion were evaluated in the CUMS, followed by brain-derived neurotrophic factor (BDNF), its tropomyosin-related kinase receptor B (TrkB), and the downstream target synapsin I expressions in the hippocampus. Results. Anhedonia, which occurred within week 2, was rapidly ameliorated by nobiletin. While fluoxetine needed additional 2 weeks to improve the anhedonia. In addition, nobiletin administration for 5 weeks significantly ameliorated CUMS-induced increase in serum corticosterone levels. Furthermore, we also found that CUMS-induced deficits of hippocampal BDNF, TrkB, and synapsin I were ameliorated by nobiletin. Conclusions. Taken together, these findings suggest that nobiletin produces rapidly acting antidepressant-like responses in the CUMS and imply that BDNF-TrkB pathway may play an important role in the antidepressant-like effect of nobiletin.